Roman military equipment : from the Punic Wars to the fall of Rome - Bishop, M. C. (Oxbow, 2006)
This is a complete revision of the original text and illustrations, which takes into account all the latest finds since the first publication of the book in 1993, as well as various constructive comments offered in published reviews.